2020
DOI: 10.1126/sciimmunol.abd1554
|View full text |Cite
|
Sign up to set email alerts
|

Immunophenotyping of COVID-19 and influenza highlights the role of type I interferons in development of severe COVID-19

Abstract: Although most SARS-CoV-2-infected individuals experience mild coronavirus disease 2019 (COVID-19), some patients suffer from severe COVID-19, which is accompanied by acute respiratory distress syndrome and systemic inflammation. To identify factors driving severe progression of COVID-19, we performed single-cell RNA-seq using peripheral blood mononuclear cells (PBMCs) obtained from healthy donors, patients with mild or severe COVID-19, and patients with severe influenza. Patients with COVID-19 exhibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

71
878
4
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 785 publications
(993 citation statements)
references
References 38 publications
71
878
4
3
Order By: Relevance
“…cMo3 have moderate expression of CD33, CD36, and much lower expression of HLA-DR than do cMo1 and cMo2. Although we and others (30) observe an increase in classical monocytes amongst COVID-19 patients, the cMo1, cMo3 subsets specifically increased, whereas cMo2 decreased, with disease severity (Fig. 2D).…”
Section: Classical Monocyte Heterogeneity In Covid-19contrasting
confidence: 44%
“…cMo3 have moderate expression of CD33, CD36, and much lower expression of HLA-DR than do cMo1 and cMo2. Although we and others (30) observe an increase in classical monocytes amongst COVID-19 patients, the cMo1, cMo3 subsets specifically increased, whereas cMo2 decreased, with disease severity (Fig. 2D).…”
Section: Classical Monocyte Heterogeneity In Covid-19contrasting
confidence: 44%
“…Introduction: The advent of single-cell RNA sequencing (scRNA-seq) has enabled the interrogation of heterogeneous cell populations in blood without cell type isolation and has already been employed in the study of myriad immune-related diseases. 14,15,18 Recent studies employing scRNA-seq to study the role of immune cell subpopulations between healthy and ill patients, such as those for Crohn's disease 41 , Tuberculosis 40 , and COVID-19 39 , have identified cell typespecific disease relevant signatures in peripheral blood immune cells; however, these types of studies have been limited to large volume venous blood draws which can tax already ill patients, reduce the scope of studies to populations amenable to blood draws, and often require larger research teams to handle the patient logistics and sample processing costs and labor. In particular, getting repeated venous blood draws within a single day and/or multiple days at the subject's home has been a challenge for older people with frail skin and those on low dosage Acetylsalicylic acid.…”
Section: Resultsmentioning
confidence: 99%
“…It was suggested that production of interferon (IFN)-α , a major anti-viral cytokine, was decreased in the most severe patients, as compared to those with moderate disease 8 . However, a recent study argued that an increased IFN-α production might contribute to the pathogenic inflammatory response 14 . Other anti-viral mechanisms and their cellular source yet remain to be studied.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we performed a high-resolution single cell RNA sequencing (scRNAseq) analysis of all APC subsets in the peripheral blood of COVID-19 patients. A pre-enrichment step enabled the characterization of even rare DC subsets, not captured in previous scRNAseq studies 14,22 . This revealed previously unrecognized multi-process defects in anti-viral defense.…”
Section: Introductionmentioning
confidence: 99%